2017
DOI: 10.1111/apt.14109
|View full text |Cite
|
Sign up to set email alerts
|

Review article: hepatitis E—a concise review of virology, epidemiology, clinical presentation and therapy

Abstract: SummaryBackground: Hepatitis E virus (HEV) is a leading cause of acute icteric hepatitis and acute liver failure in the developing world. During the last decade, there has been increasing recognition of autochthonous (locally acquired) HEV infection in developed countries. Chronic HEV infection is now recognised, and in transplant recipients this may lead to cirrhosis and organ failure.Aim: To detail current understanding of the molecular biology of HEV, diagnostic and therapeutic strategies and propose future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 140 publications
1
78
0
2
Order By: Relevance
“…The results of our exposure analysis are important because they are consistent with others’ and our previous findings, stressing the role of certain dietary habits in determining the spread of HEV infection in some geographic areas …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of our exposure analysis are important because they are consistent with others’ and our previous findings, stressing the role of certain dietary habits in determining the spread of HEV infection in some geographic areas …”
Section: Discussionsupporting
confidence: 91%
“…Studies conducted among the general population and blood donors in Europe found variable anti‐HEV seroprevalence rates, with important variation even within the same country . Despite the lack of a concerted satisfying definition of the levels of HEV endemicity, also in Europe some areas showing seroprevalence rates approaching to and over 50% have been classified as hyperdendemic . The great variability in prevalence was also confirmed by comparing studies using the same anti‐HEV assay .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In most symptomatic patients with no underlying conditions, an HEV infection resembles typical acute viral hepatitis and usually resolves spontaneously . However, in immunocompromised patients, HEV can cause chronic infections that last longer than 3 months . An understanding of the viral mutations that arise in patients with an impaired or weakened immune response may yield insights into fundamental viral mutational patterns and biases, as well as the rate of turnover in dominant viral sequence.…”
Section: Introductionmentioning
confidence: 99%